Taxonomic updates on the Mecocephala group (Hemiptera: Pentatomidae): Redescription of ‘Hypatropis complex’, with a review of genitalic terminology and new records - Barros, Lurdiana D.; Barão, Kim R.; Grazia, Jocelia (Zootaxa, 2021)
The taxonomic revision of ‘Hypatropis complex’, composed by Amauromelpia Fernandes & Grazia, Hypatropis Bergroth, Luridocimex Grazia, Fernandes & Schwertner, Stysiana Grazia, Fernandes & Schwertner, and Pedinonotus Fernandes & Grazia, updating the genitalic terminology, are presented here. The differential diagnosis of ‘Hypatropis complex’ and all of its members are provided. Photographs of the type-specimens and genitalia, species distributional map with new records, and a key to genera and species are also provided.